COGNITIVE EDUCATION IS A POWERFUL WEAPON OF LEARNING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article considers cognitive education, its types and technologies. Cognitive technologies allow not only influencing human behavior, but also to predict and analyze information.